Pharmacological treatment of hepatocellular carcinoma with cavoatrial tumor thrombus – case series and literature review - Zhan, Tianzuo; Sollors, Janina; Steinebrunner, Niels; Schlitt, Hans Jürgen; Stroszczynski, Christian; Weiss, Karl Heinz; Ebert, Matthias P.; Teufel, Andreas (Zeitschrift für Gastroenterologie, 2019)
Hepatocellular carcinomas (HCC) that extend into the vena cava and the right atrium have a poor prognosis. Surgical approaches including partial hepatectomy and thrombectomy are the most frequently reported treatment options. However, most patients with advanced HCC are not eligible for complex surgical interventions due to reduced liver function, comorbidities, and metastases. At the same time, systemic treatment options of HCC have expanded in recent years. Here, we report 3 cases of patients with advanced HCC who developed a cavoatrial tumor thrombus (CATT) after initial surgical or interventional therapy. The patients were consequently treated with sorafenib or nivolumab. In all cases, the tumor responded to systemic treatment with disease stabilization or partial regression. Overall survival after diagnosis of CATT was 3 and 17 months for sorafenib and 7 + months for nivolumab. Compared to survival rates of alternative treatment options, systemic therapies demonstrated comparable outcomes. In summary, pharmacotherapy is an efficient and well worth option to treat patients with HCC and CATT and should be an integral part of a multimodal therapy concept.
Keywords: liver; hepatitis C; hepatitis B; HCC; immunotherapy; liver cirrhosis